Altered cerebral perfusion in children with Langerhans cell histiocytosis after chemotherapy. Issue 3 (4th December 2019) - Han, Michelle; Kim, Lily H.; Shpanskaya, Katie; Kim, Christine; Iv, Michael; Jeng, Michael; Yeom, Kristen W.
Abstract: Background and purpose: Children with Langerhans cell histiocytosis (LCH) may develop a wide array of neurological symptoms, but associated cerebral physiologic changes are poorly understood. We examined cerebral hemodynamic properties of pediatric LCH using arterial spin‐labeling (ASL) perfusion magnetic resonance imaging (MRI). Materials and methods: A retrospective study was performed in 23 children with biopsy‐proven LCH. Analysis was performed on routine brain MRI obtained before or after therapy. Region of interest (ROI) methodology was used to determine ASL cerebral blood flow (CBF) (mL/100 g/min) in the following bilateral regions: angular gyrus, anterior prefrontal cortex, orbitofrontal cortex, dorsal anterior cingulate cortex, and hippocampus. Quantile (median) regression was performed for each ROI location. CBF patterns were compared between pre‐ and posttreatment LCH patients as well as with age‐matched healthy controls. Results: Significantly reduced CBF was seen in posttreatment children with LCH compared to age‐matched controls in angular gyrus ( P  = .046), anterior prefrontal cortex ( P  = .039), and dorsal anterior cingulate cortex ( P  = .023). Further analysis revealed dominant perfusion abnormalities in the right hemisphere. No significant perfusion differences were observed in the hippocampus or orbitofrontal cortex. Conclusion: Perfusion in specific cerebral regions may be consistently reduced in children with LCH, and may represent effects of underlying disease physiology and/or sequelae of chemotherapy. Studies that combine a formal cognitive assessment and hemodynamic data may further provide insight into perfusion deficits associated with the disease and the potential neurotoxic effects in children treated by chemotherapy.